Flow-Through Flaps in the Absence of an Arterial Gap for Extremity Defect Reconstruction: Minimizing the Donor-Site Morbidity - Fernandez-Garrido, Manuel; Lopez Penha, Tiara R.; Qiu, Shan Shan (Journal of Reconstructive Microsurgery, 2019)
Background The use of flow-through flaps was popularized in the early 1990s by Costa, Soutar and Lamberty in cases where an arterial gap was present or a major artery of the limb was damaged. We hypothesized that flow-through flaps can be used in all extremity reconstruction cases, where there is an indication for a free-flap, irrespective of the existence of arterial defect due to its many advantages while not increasing the flap loss significantly.Methods A retrospective study was performed by examining patient status and surgery reports of all patients who underwent extremity reconstruction with a flow-through flap from January 2011 to January 2016. This procedure was applied to all the patients, irrespective of the presence of an arterial gap.Results Forty-seven patients were included. The most frequently used flaps were the anterolateral thigh flap and the latissimus dorsi flap. Reconstructions were either posttraumatic or after oncological resection. Two cases of flap loss were encountered. The mean total operating time was 480 ± 153 minutes. The mean follow-up was 10 ± 3 months. There were no donor-site wound complications.Conclusion Based on our results, the flow-through flap technique can be considered a safe alternative to the end-to-side technique for complex extremity defect reconstruction irrespective of the vascular status. The additional arterial anastomosis, even in the absence of an arterial gap or a vascular compromised extremity, did not increase the complication rate in the hands of experienced microsurgeons.
Keywords: flow-through flaps; extremity reconstruction